1991
DOI: 10.1148/radiology.178.2.1987597
|View full text |Cite
|
Sign up to set email alerts
|

Simple renal cysts in children: diagnosis and follow-up with US.

Abstract: To assess the sonographic frequency of simple renal cysts in children, the authors retrospectively reviewed the results of abdominal sonographic studies of 16,102 children performed over a 5-year period between January 1, 1985, and December 31, 1989. Patients with abnormal renal function, dysplastic kidneys, or a family history of polycystic kidney disease were excluded from the study. The authors' review of the sonograms revealed 37 simple cysts in 35 patients (0.22%); the cysts were evenly distributed by age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
8

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 0 publications
1
34
0
8
Order By: Relevance
“…This finding is consistent with previous data for at-risk PKD1 individuals 15 or for individuals who underwent ultrasonography for nonrenal indications. 19,20 Nonetheless, 2.1% (three of 144) and 0.7% (one of 144) of the genetically unaffected cohort younger than 30 yr had one and two renal cysts, respectively. These data highlight the need for using more stringent criteria such as three or more (unilateral or bilateral) renal cysts to minimize false-positive diagnoses in this age group.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with previous data for at-risk PKD1 individuals 15 or for individuals who underwent ultrasonography for nonrenal indications. 19,20 Nonetheless, 2.1% (three of 144) and 0.7% (one of 144) of the genetically unaffected cohort younger than 30 yr had one and two renal cysts, respectively. These data highlight the need for using more stringent criteria such as three or more (unilateral or bilateral) renal cysts to minimize false-positive diagnoses in this age group.…”
Section: Discussionmentioning
confidence: 97%
“…(The average diameter of the cysts in the study of Gordon was 3.5 cm.) In a more recent article published by McHugh et al [4], it was found that the incidence of renal cysts in children, as detected by US, was 0.22%. In that particular study, the authors reviewed retrospectively 16,102 abdominal US examinations of children aged between birth and 18 years.…”
Section: Discussionmentioning
confidence: 95%
“…Sağ-lıklı çocukların %0,3'ünde basit böbrek kisti vardır. 61 Renal kistlerde, bilgisayarlı tomografi (BT) görüntü-leri için hazırlanan, ancak MRG ve ultrasonografi (USG) de kullanılabilen Bosniak renal kist klasifikasyon sistemi geliştirilmiştir (Tablo 1). [62][63][64] Bu sistem, BT'de görülen renal kistteki sıvı dansitesine, kistin duvar ve septa kalınlığına ve kist duvarında kalsifikasyon olup olmamasına dayanmaktadır.…”
Section: Basi̇t Ki̇stlerunclassified